2019
DOI: 10.3389/fvets.2019.00282
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antimicrobial and Anti-inflammatory Properties of Bacillus-DFM (Norum™) in Broiler Chickens Infected With Salmonella Enteritidis

Abstract: Restrictions of in-feed antibiotics use in poultry has pushed research toward finding appropriate alternatives such as Direct-Fed Microbials (DFM). In this study, previously tested Bacillus isolates ( B . subtilis and B . amyloliquefaciens ) were used to evaluate their therapeutic and prophylactic effects against Salmonella enterica serovar Enteritidis ( S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 101 publications
4
29
0
Order By: Relevance
“…In accordance with previous studies, the current study found that inulin increased the abundances of Streptococcus and Lactobacillus, which were shown to be positively related to butyrate production (Yan et al, 2017). Streptococcus, Lactobacillales, and Firmicutes exhibited a positive relationship with acetate production in the present study, playing an important role in reducing the colonization and incidence of SE through reducing the pH and competitive exclusion (Adhikari et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous studies, the current study found that inulin increased the abundances of Streptococcus and Lactobacillus, which were shown to be positively related to butyrate production (Yan et al, 2017). Streptococcus, Lactobacillales, and Firmicutes exhibited a positive relationship with acetate production in the present study, playing an important role in reducing the colonization and incidence of SE through reducing the pH and competitive exclusion (Adhikari et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…CON (n = 3): basal diet without inulin supplementation; SE (n = 3): Salmonella-infected chicken fed with basal diet; 0.5% InSE (n = 3): Salmonella-infected chicken fed with 0.5% inulin; 1% InSE (n = 3): Salmonella-infected chicken fed with 1% inulin. a vital role in reducing the colonization and incidence of SE (Adhikari et al, 2019). In this study, inulin also increased the abundance of Streptococcus.…”
Section: Discussionsupporting
confidence: 63%
“…Even so, this outcome is not new in our laboratory’s experience translating in vitro data to in vivo efficacy. We have observed similar results with other probiotic bacteria against Salmonella enteritidis [ 25 ], or biodegradation of aflatoxin B1 [ 26 ], as well as other nutraceuticals showing significant and encouraging reductions against Histomonas meleagridis in vitro, but none of which translated to effectivity in vivo [ 27 , 28 ]. Hence, in vitro biological effects do not always draw a parallel result when tested in live animals.…”
Section: Discussionsupporting
confidence: 77%
“…DFMs are viable, naturally occurring microbial cultures, including bacteria belonging to the genera Lactobacillus, Enterococcus, Streptococcus, Bifidobacterium, and Propionibacterium, which when fed to the host animal, generate a beneficial health response through their ability to modulate the diversity and composition of the gut microbiota. Various species of Bacillus also have been tested as DFMs on the basis of their ability to inhibit pathogens by producing antimicrobials (13)(14)(15). Bacillus has the added advantage as a DFM of producing spores that are resistant to low pH, bile salts, and other harsh conditions of the gastric environment (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%